Safety recovery zone corridor for malaysian roads derived from live field experiments - Kunji, Ahmad Kamal; Ali, Nasly Mohamed; Zulkiple, Adnan
The increasing number of high impact run-off-road accidents has alarmed institutions to carry out studies to formulate roadside geometric design guideline that could reduce the number of fatalities and severe injuries. Currently, Malaysia has not issued a roadside geometric design guide that requires provision of roadside safety recovery zone corridor. Establishing a configuration and dimension of the roadside slope cross-section that allow straying off from travel lanes will reduce run-off-road fatal accidents or severe injuries for motorists safe traversing back into driving lanes. Live field experiments were carried out to determine the optimum roadside safety recovery zone corridor widths for roads in Malaysia. The ten test locations were selected from four states namely Pahang, Johor, Selangor and Perak of Malaysia with various roadside slope gradients and ground surface conditions. The study shows that safety recovery zone corridor widths increase with the increase of the roadside slope gradients and vehicle travelling speeds. Depending on the road design standard types, the safety recovery zone corridor widths for both rural and urban roads range between 1.52 to 8.06 metres for vehicle speed between 50 km/h to 110 km/h and roadside gradients between 1V:10H and 1V:4H.